The following steps of solving for the roots of 2x² - 4x -3 = 0 were retrieved from another source Step 1 2x² - 4x = 3 Step 2 2(x² - 2x) = 3 Step 3 2(x² - 2x + 1) = 3 + 1 Step 4 2(x - 1)² = 4 From this, we can see that on Step 3, Tran made a mistake of adding 1 to 3. As we can see, 2(x² - 2x + 1) = 2x² - 4x + 2. That means, instead of adding 1, it should have been 2. Therefore, the step that Tran first made an error is Step 3.
Answer:
the answer is 2
Step-by-step explanation:
The polynomial 16a² - 4a + 4a - 1 can be simplified to a difference of squares
Polynomial is an expression that involves only the operations of addition, subtraction, multiplication of variables.
The difference of two squares is given by:
a² - b² = (a + b)(a - b)
Hence:
16a² - 4a + 4a - 1 = 4a(4a - 1) + 1(4a - 1)
= (4a + 1)(4a - 1)
The polynomial 16a² - 4a + 4a - 1 can be simplified to a difference of squares
Find out more on polynomial at: brainly.com/question/2833285
False
Answer:
The sentence is True
Step-by-step explanation:
In Geometry, there is a theorem that relation the sine angle and the cosine angle. The theorem says: The sine of any acute angle is equal to the cosine of its complement.
So, let β represent an acute angle
sin (β)=cos(90-β)
Given β=30, let it replace in the formule:
sin (30)=cos(90-30)
sin (30)=cos(60)
Done.